Analysis of Secondary Particles Produced by 50-500 MeV Muon and Water Interaction using PHITS Monte Carlo Package - Yani, Sitti; Hidayatuloh, Dadan; Sumaryada, Tony (Jurusan Fisika FMIPA Universitas Andalas, 2024)
Secondary particles will always be generated in particle-to-matter interactions. The interaction of muons with matter produces various secondary particles. In this study, secondary particles produced by the interaction between muons with energies of 5, 50, 100, 200 and 500 MeV with water were analyzed using the PHITS Monte Carlo package. The muon source is placed on the surface of water that has a thickness of 1 km. The muography technique was applied by placed a detector at a depth of 1 km from the source. This detector records the secondary particles produced by the interaction. The results obtained show that this interaction produces secondary particles in the form of photons and neutrons in the detector. The number and energy of these photons and neutrons are strongly influenced by the initial energy of the muon. Muons with the lowest energy of 5 MeV produce more secondary particles than any other energy by a factor of 10. Low-energy muons travel slowly, allowing more interactions to occur and increasing the number of secondary particles in the detector. The energies of neutrons and photons in the detector are at most 3.76 MeV and 5.3 MeV, respectively.